Effect of Change in Preoperative Depression on Patient Outcomes Following Lumbar Spine Surgery. (16th November 2020) - Park, Christine; Trepte, Alessandra N.G; Cook, Chad; Gottfried, Oren N
Abstract: INTRODUCTION: Depression is a common comorbidity in patients undergoing spine surgery. Patients with depression are more likely to have negative outcomes such as poor quality of life, worse perception of pain, and higher all-cause mortality postoperatively. METHODS: This was an observational study including 11, 049 adult patients with improvement in their preoperative diagnosis of depression who underwent lumbar spine surgery in the Quality Outcomes Database (QOD) from 2012 to 2018 with either a 12- or 24-month follow-up. Improvement in depression was assessed through baseline and 3-month follow-up phone calls and an online survey sent after surgery. Patients were given the choices of "Not depressed, " "Moderately depressed, " and "Severely depressed" to describe their status. Clinical outcomes measured included Oswestry Disability Index (ODI), Numeric Rating Scale (NRS) back pain (BP) and leg pain (LP), health-related quality of life (HRQOL), and patient satisfaction measured at 12- and 24 months after surgery. RESULTS: Of the 9, 656 and 1, 393 patients who were included in the 12- and 24-month cohort, respectively, 7, 277 patients (75.4%) and 1, 089 (78.2%) experienced improvement in depression within three months after lumbar spine surgery. At both 12- and 24-month follow-up, patients who had improved depression also had improvement in ODI (12-month OR = 3.21 [95% CI 2.89-3.56]; 24-month OR = 2.68 [95% CI 2.01-3.56]), BP (12-month OR = 2.27 [95% CI 1.96-2.48]; 24-month OR = 2.01 [95% CI 1.49-2.73], LP (12-month OR = 2.38 [95% CI 2.12-2.67]; 24-month OR = 1.73 [95% CI 1.26-2.38], HRQOL (12-month OR = 2.36 [95% CI 2.04-2.74]; 24-month OR = 1.85 [95% CI 1.23-2.79], and patient satisfaction (12-month OR = 2.67 [95% CI 2.36-3.01]; 24-month OR = 1.53 [95% CI 1.09-2.16], all P  < .01). CONCLUSION: Depression is an important comorbidity to consider in patients undergoing lumbar spine surgery. Improvement in depression can result in concurrent improvement in patient-reported outcomes and quality of life.